The global agenda : issues and perspectives - Kegley, Charles W.; Wittkopf, Eugene R., 1943- (Boston : McGraw-Hill, 2001)
This work is incisive in its coverage of key concepts, issues and theoretical and prescriptive approaches to the interpretation of world politics. The readings are broad based, balanced, and are categorized into four areas that build on the distinction between high and low politics.
Machine derived contents note: Preface -- Part I Arms and Influence -- 1 Power, Capability, and Influence in International Politics -- K.J. Holsti -- 2 Power and Interdependence in the Information Age -- Robert O. Keohane and Joseph S. Nye, Jr. -- 3 The Role of Military Power in the Third Millennium -- Bjorn Moller -- 4 War and Its Causes -- Jack S. Levy -- 5 The Obsolescence of Major War -- John Mueller -- 6 Nuclear Weapons Threaten Our Existence -- Paul H. Nitze -- 7 The New Threat of Mass Destruction -- Richard K. Betts -- 8 Terror's New Face: The Radicalization and Escalation of Modern Terrorism -- Walter Laqueur -- 9 The Trouble with Sanctions -- Robert A. Sirico -- 10 The Changing Nature of World Power -- Joseph S. Nye, Jr. -- Part II Discord and Collaboration -- 11 Models of International Relations: Realist and Neoliberal Perspectives on Conflict and Cooperation -- Ole R. Holsti -- 12 Managing the Challenge of Globalization and Institutionalizing Cooperation Through Global Governance -- David Held and Anthony McGrew, with David Goldblatt and Jonathan Perraton -- 13 What to Do with American Primacy -- Richard N. Haass -- 14 Building Peace in Pieces: The Promise of European Unity -- Donald J. Puchala -- 15 Managing Conflict in Ethnically Divided Societies: A New Regime Emerges in the 1990s -- Ted Robert Gurr -- 16 The New Interventionism and the Third World -- Richard Falk -- 17 The Coming Clash of Civilizations: Or, the West Against the Rest -- Samuel P. Huntington -- 18 Human Rights: From Low to High Politics in International Relations -- David P. Forsythe -- 19 The Institutional Maintenance of Twenty-First Century World Order -- Harvey Starr -- 20 How Democracy, Interdependence, and International Organizations Create a System for Peace -- Bruce Russett -- 21 The Reality and Relevance of International Law in the Twenty-First Century -- Christopher C. Joyner -- Part 3 Politics and Markets -- 22 Three Ideologies of Political Economy -- Robert Gilpin -- 23 Whose "Model" Failed? Implications of the Asian Economic Crisis -- Linda Y.C. Lim -- 24 The World Is Ten Years Old: The New Era of Globalization -- Thomas L. Friedman -- 25 Workers of the World, Now What? -- Kathleen Newland -- 26 Competitiveness: A Dangerous Obsession -- Paul Krugman -- 27 Dollarization: More Straightjacket than Salvation -- Jeffrey Sachs and Felipe Larrain -- 28 Global Rules for Global Finance -- Ethan B. Kapstein -- 29 The WTO and Nonmarket Economies -- Greg Mastel -- 30 The Brave New Wired World -- Daniel F. Burton, Jr. -- 31 Life Is Unfair: Inequality in the World -- Nancy Birdsall -- Part 4 Ecology and Politics -- 32 Entering the Twenty-First Century -- John L. Petersen -- 33 Ecology Myths: One Planet, One Experiment -- Paul R. Ehrlich and Anne H. Ehrlich -- 34 Do We Consume Too Much? -- Mark Sagoff -- 35 Dietary Implications of the Globalization of the Food Trade -- Tim Lang -- 36 Encroaching Plagues: The Return of Infectious Disease -- Laurie Garrett -- 37 Climate Change: Can the North and South Get in Step? -- Seth Dunn -- 38 The Next Doubling: Understanding Global Population Growth -- Jennifer D. Mitchell -- 39 Gray Dawn: The Global Aging Crisis -- Peter G. Peterson -- 40 Environment, Scarcity, and Violence -- Thomas Homer-Dixon -- 41 The Tragedy of the Commons in Global Perspective -- Marvin S. Soroos.
Includes bibliographical references.
Keywords: Since 1989; International relations; International economic relations; Globalization; World politics -- 1989-; Relations internationales